A Rare Case of Oropharyngeal Leech Infestation Causing Epistaxis and Dysphagia in a Child in Herat, Afghanistan: A Case Report - Seyed Abdul Ahad Wadoodi; Said Abdul Kabir Hawari; Mohammad Masudi; Ali Rahimi; Nasar Ahmad Shayan (Clinical Case Reports, 2026)
ABSTRACT Oropharyngeal leech infestation is rare. A 12‐year‐old Afghan girl developed recurrent epistaxis, dysphagia, throat irritation, and cough after drinking untreated stream water. Examination revealed an 8‐cm leech attached to the posterior pharynx. Forceps removal immediately resolved symptoms. Leech infestation should be considered following freshwater exposure in endemic rural settings worldwide.